2020
DOI: 10.1038/s41598-020-64416-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal osmotic and neurometabolic changes in young rats with chronic cholestatic liver disease

Abstract: type c hepatic encephalopathy (type c He) is increasingly suspected in children with chronic liver disease (CLD), and believed to underlie long-term neurocognitive difficulties. The molecular underpinnings of type c He in both adults and children are incompletely understood. in the present study we combined the experimental advantages of in vivo high field 1 H magnetic resonance spectroscopy with immunohistochemistry to follow longitudinally over 8 weeks the neurometabolic changes in the hippocampus of animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 53 publications
(80 reference statements)
2
21
0
Order By: Relevance
“…Experimental models with rats developing chronic liver disease early in life have demonstrated pronounced neurometabolic changes. 18 Early onset of liver disease in children has been associated with neurocognitive impairment. 1,[13][14][15]19,20 Malnutrition may contribute, and impaired growth has been identified as a predictor of poor neurocognitive -2021…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models with rats developing chronic liver disease early in life have demonstrated pronounced neurometabolic changes. 18 Early onset of liver disease in children has been associated with neurocognitive impairment. 1,[13][14][15]19,20 Malnutrition may contribute, and impaired growth has been identified as a predictor of poor neurocognitive -2021…”
Section: Discussionmentioning
confidence: 99%
“…In this context, ligation of the bile‐duct can also be performed in young rats (i.e. 15 or 21 days after birth) leading to a model of type C HE in the developing brain 152 Differences between gender in children with biliary atresia have been observed, 153 with more women presenting with cholestatic liver disease than men.…”
Section: Current Animal Models Of Hementioning
confidence: 99%
“…For instance, cirrhotic patients who died from hepatic coma had reduced glutamate concentration in brain regions associated with HE [123,131]. Similarly, studies in cirrhotic-BDL rats have shown that glutamate concentration depletion in the hippocampus was correlated with systemic ammonia levels [132]. Overall, disrupted glutamate homeostasis has been well documented in HE, however the implications of glutamate excitotoxicity in neuronal cell death remains poorly defined.…”
Section: Healthy Astrocyte = Healthy Neuronmentioning
confidence: 99%